Supporting Local Beauty: Analyzing the Motivations Behind Consumer Purchase Intention in the Skincare Industry - Satyawati, Anak Agung Ayu; Mahyuni, Luh Putu (Yayasan Sinergi Kawula Muda, 2025)
This study explores consumer purchase intentions for Somethinc, a leading Indonesian skincare brand, examining factors like influencers, product quality, customer reviews, viral marketing, and pricing in the competitive skincare market. It addresses the challenge of understanding consumer interest in local brands amid global competition, with a focus on the moderating role of service quality. A quantitative approach was employed using survey data collected from 428 Somethinc Instagram followers through online questionnaires. The questionnaire included validated scales measuring influencer impact, product quality, customer reviews, viral marketing, pricing, service quality, and purchase intention. The data were analyzed using Structural Equation Modeling (SEM) with PLS to assess the relationships among variables and test the moderating effect of service quality. The findings show that influencers, product quality, customer reviews, viral marketing, and pricing positively impact purchase intention, while service quality does not significantly moderate the relationship between product quality and purchase intention. The study highlights the importance of credible influencers, appealing packaging, positive reviews, viral marketing, and competitive pricing in driving consumer interest in local skincare products.